Applicability of the Intelligence-Led Policing Model in Brazil: The Case of the Military State Police of Santa Catarina - Rafael Wohlemberg Rossi; Carlos Roberto de Rolt; Luis Antonio Pittol Trevisan (Journal of Systemics, Cybernetics and Informatics)

(untitled)
This article discusses scientific issues and evidence regarding the policing intelligence-led model (ILP) in police institutions and its applicability in the organizational reality of the Military Police of Santa Catarina (PMSC). This is a theoretical-analytical study with a qualitative approach through a systematic and narrative review of national and international academic production. The research on the subject was found to be incipient in the Brazilian scenario, although space has been gained in several other countries, with a reasonable number of studies. The adoption of intelligence-led policing has the power to "unify" police work, enhance preventive action in public safety, and improve the strategic management of police organizations.